How to build a retail website that keeps on selling - Singapore Management University (Institutional Knowledge at Singapore Management University, 2018)
E-commerce appeal is a dynamic art and firms need to keep up With e-commerce giant Amazon launching its online retail service in Australia to a muted reception, new research from Eric Lim and his colleagues, Fei Liu, Bo Xiao and Chee-Wee Tan, on the impact of product appeal and website quality on online purchases is timely.